The Effect of Greenwashing, Green Word of Mouth, Green Trust and Attitude towards Green Products on Green Purchase Intention - Mayumi Kris Ghassani; Nadhiv Arifata Rahman; Trisha Geraldine; Ina Agustini Murwani (Budapest International Research and Critics University, 2022)
Greenwashing has begun in developing countries, like Indonesia. Enterprises have begun selling their products as